Re-conceptualizing safe spaces : supporting inclusive education - Winter, Kate; Bramberger, Andrea (Emerald Publishing Limited, 2021)
A 'safe space' is both a precondition, and one of the effects, of efforts of inclusiveness and egalitarian access to education. By creating safe spaces for learning and unlearning, researchers and practitioners have been working to strengthen the purpose of schools and universities, where education and learning are intended for everyone, with the goal of increasing critical thinking and valuing difference. Re-Conceptualizing Safe Spaces broadens the idea of a safe space that is traditionally discussed in feminist studies, to include gendered identities intersecting with class, race/ethnicity, sexual orientation, and ability within multiple aspects of education. This edited collection showcases work supporting access to education of persistently marginalized individuals, as well as efforts that help privileged groups understand their role in perpetuating the marginalization of others in educational spaces, by bringing into the popular discourse examples of the diverse and valuable work taking place. Combining foundational concepts with practical cases of creating safe spaces in venues of education, this book is essential reading for educators across the USA, Europe, and beyond.